(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The Taxes role is changing in economic life ,with the economic it was system of nature was changed trucked in differences countries, pit is providing financial resources ,prevent economic fluctuation, achieving economic and social balance. Iraq is one of countries which have adopted on the fiscal policy as a mean to achieve economic and social balance through the of inequalities in income distribution that made the additional targets to activate its conterbution in financial ecounomy and social targets together